CHART CONTROL OF CALIBRATION FUNCTIONAL WITH ASSUMPTION OF VARIANCE OF MEASUREMENT ERRORS KNOWN - DOMINGOS FILHO, Manoel; SAMOHYL, Robert Wayne (Brazilian Journal of Biometrics, 2016)
This article has as its main objective the construction of control charts using the calibration model functional. For this purpose it is assumed that the variance of measurement errors involved in calibration model functional is known, or can be estimated, because this is one of the conditions of regularity of calibration model functional. More precisely, the assumption of knowing one of the variances of the errors makes the functional model is feasible, that is, makes it possible to estimate the parameters of the model. It is believed, also, that the measurement errors of dependent and independent variables are additives and normally distributed.